EMPIRICAL ETHICS AND ITS ALLEGED META-ETHICAL FALLACIES - Vries, Rob De (Bioethics, 2009)
This paper analyses the concept of empirical ethics as well as three meta-ethical fallacies that empirical ethics is said to face: the is-ought problem, the naturalistic fallacy and violation of the fact-value distinction. Moreover, it answers the question of whether empirical ethics (necessarily) commits these three basic meta-ethical fallacies.